The incidence and mortality of cancer in Eastern Mediterranean Regional Office (EMRO) and its relationship with Human Development Index (HDI): An Ecological Study - Khazaei, zaher; Navabi, Mojgan; Darvishi, Isan; goodarzi, Elham (Asian Pacific Journal of Environment and Cancer, 2018)
Background: the cancer was considered as the second cause of mortality in the developed countries and all around the world after the cardiovascular diseases. Also, it was reported as the third cause of mortality in the less developed countries after cardiovascular diseases. The current study was aimed to evaluate the epidemiology, incidence, and mortality of all cancers in East-Mediterranean region by gender and age. Methods: This study was an ecologic study in Asia for assessment of the correlation between age-specific incidence rate (ASIR) and age-specific mortality rate (ASMR) with HDI (life expectancy at birth, mean years of schooling and gross national income (GNI) per capita) Data about SIR and SMR for every Asian country for the year 2012 were obtained from the global cancer project. Correlation bivariate method for assessment of the correlation between incidence and mortality rates was used. Statistical analysis using Stata-14 and P 05/0, respectively and a significant <0.05. Results: in East-Mediterranean region, some 555318 cases of cancer recorded in 2012. The highest incidence rates of cancer were reported for breast, colo-rectum, lung, liver, and bladder being 17.9%, 5.9%, 5.9%, 5.3%, and 5%, respectively. Also, the highest mortality of cancer were reported for breast, colo-rectum, lung, liver, and bladder being 11.5%, 5.8%, 5.9%, 7.6%, and 3.8%, respectively. The highest and lowest mortality ratios were reported for Somalia, and Saudi Arabia being 106.2, and 53.9 cases per 100000 people, respectively. Lung cancer and Human Development Index (HDI) had significant correlation with each other (P> 0.05). Also, a significant correlation was seen between Human Development Index (HDI) and mortality rates of breast, colorectal, lung and liver cancer (P> 0.05). Conclusion: the cancer was considered as one of the main causes of mortality in the most countries of East-Mediterranean region. The breast and colorectal cancers were reported as the most common types of cancer in this region. As for the alarming trend and remarkable distribution of cancer to the disease load in East-Mediterranean countries, controlling the cancer should be considered as one of the priorities of health policy. Key words: Cancer, Incidence, Mortality, Eastern Mediterranean Regional Office (EMRO).